How advances in low-g plumbing enable space exploration - M. M. Weislogel (npj Microgravity, 2022)
Abstract In many ways, plumbing is essential to life support. In fact, the advance of humankind on Earth is directly linked to the advance of clean, healthy, reliable plumbing solutions. Shouldn’t this also be true for the advancement of humankind in space? Unfortunately, the reliability of even the simplest plumbing element aboard spacecraft is rarely that of its terrestrial counterpart. This state of affairs is due entirely to the near-weightless “low-g” state of orbiting and coast spacecraft. But the combined passive capillary effects of surface tension, wetting, and system geometry in space can be exploited to replace the passive role of gravity on earth, and thus achieve similar outcomes there. In this paper, we review a selection of experiments conducted in low-g environments (i.e., ISS and drop towers) that focus on capillary fluidic phenomena. The results of each experiment are highly applicable to subsequent advances in spacecraft plumbing. With examples ranging from spurious droplet ejections to passive bubble coalescence, to droplet bouncing, to complex container wicking, we show how simple low-g demonstrations can lead to significant reliability improvements in practical passive plumbing processes from pipetting to liquid-gas separations, to wastewater transport, to drinking in space.